Erupted compound odontoma: Report of a rare case - Lakshmi Kavitha Nadendla (Journal of Oral and Maxillofacial Radiology, 2013)
Odontomas are the most common type of odontogenic tumors and are generally asymptomatic. They are usually discovered on routine radiographic examination. Frequently it may interfere with the eruption of the teeth. Eruption of odontoma into the oral cavity is very rare. We report a case of an asymptomatic erupted compound odontoma in an 18-year-old female patient, situated between right mandibular canine and lingually placed right lateral incisor, causing crowding of lower anterior teeth, along with a brief review of the literature.